Near‐Room‐Temperature Quasi‐Solid‐State F‐Ion Batteries with High Conversion Reversibility Based on Layered Structured Electrolyte. Issue 12 (20th January 2023) - Yu, Yifan; Lei, Meng; Li, Decheng; Li, Chilin
Abstract: Solid‐state fluoride ion batteries (SSFIBs) are anion‐shuttle‐driven and alkali‐metal‐free emerging energy storage systems, and have the advantages of low cost, high safety, and energy density. However, the current major challenges of SSFIBs or quasi‐SSFIBs are the lack of high‐conductivity fluoride electrolytes and the difficulty of mild‐temperature operation of full cells. Here, a 2D fluoride conductor (KSn2 F5 ) synthesized by mechanochemical method is employed as the compatible solid electrolyte with a high F‐ion conductivity of 10 −4 S cm −1 at 60 °C. The high concentration and frequent hopping of charge carriers in F‐vacancy‐rich KSn2 F5 contribute to the higher ionic conductivity compared to most reported fluoride structures. Integrating this layered electrolyte with high‐voltage CuF2 cathode and Sn/SnF2 anode, a highly reversible cycling of conversion‐type quasi‐SSFIBs with a discharge capacity of 150 mAh g −1 for at least 70 cycles at 60 °C is achieved. The interface engineering aided by tetra‐ n ‐butylammonium fluoride salt facilitates the F‐ion transfer between cathode and electrolyte and fluorination/defluorination conversion mechanism of CuF2 cathode with optimized multiphase and nanodomain distributions. Abstract : A 2D fluoride conductor (KSn2 F5 ) is employed as a solid electrolyte with a high F‐ion conductivity of 10 −4 S cm −1 at 60 °C. Integrating this electrolyte with a CuF2 cathode and a Sn/SnF2 anode, a reversible cycling of conversion‐type quasi‐solid‐state F‐ion batteries is achieved with a discharge capacity of 150 mAh g −1 for at least 70 cycles at 60 °C.